Derajat Aglutinasi pada Pemeriksaan Golongan Darah Metode Tabung Berdasarkan Masa Simpan Test Sel A dan Test Sel B Hari Ke-0, Ke-2, Ke-4, Ke-6 dan Ke-8 - Karinta Syifa Zatalini; Rachmad Bayu Kuncara; Anung Sugihantono (Jaringan Laboratorium Medis, 2024)
Blood group examination is an examination that aims to determine the type of blood group. Cell test is a blood group examination reagent used to detect antibodies in the serum being examined. The long shelf life of cell tests that can only last for two days is considered less effective for agencies with a high level of blood services. The purpose of this study was to describe the degree of agglutination in blood group examination with cell test A and B stored on the 0th, 2nd, 4th, 6th, and 8th days. This study is a descriptive study with a Quasi Experimental research design. Test cell A and test cell B were made from red blood cell specimens of 3 blood type A and 3 blood type B respectively. Test cells are stored in a refrigerator with a temperature of 2-6Â° C. Test cells were then examined on the 0th, 2nd, 4th, and 6th day of storage. Calculation of samples and repetitions using the Federer formula with the number of treatments in this study is 5 treatments. Based on the calculation, one sample of test cell A and test cell B was obtained with five repetitions of each examination. The results showed that on the 0th, 2nd, 4th, and 6th day of cell test storage, the results of blood type examination were obtained, namely the degree of agglutination 4+ with erythrocytes in the cell test clumping into one bond, cells forming large agglutination with clear supernatant. On the 8th day of storage, the result of agglutination degree is 3+ with erythrocytes in test cells not clumping perfectly, there are erythrocyte granules and cloudy supernatant. Based on the results of the study, it is concluded that test cell A and test cell B can be used optimally until day 6 storage.